The overseas Chinese in ASEAN business strategies and management practices - Limlingan, Victor Simpao (Pasig Vita Development Corp., 1986)
"The objective of this book is to formulate a conceptual framework for explaining how the Overseas Chinese in the ASEAN countries have achieved remarkable economic performance. The first part of the thesis deals with validating and accounting for their economic performance. The remarkable economic performance is fact and cannot be explained away by any statistical or structural hypothesis. Moreover, historical analysis indicates that the remarkable performance cannot be explained by the Trader hypothesis. The second part deals with stating an alternative hypothesis to the disproven Trader hypothesis. The alternative hypothesis must explain how Chinese businessmen evolved from the migration of coolie laborers. The book explains the remarkable economic performance on the basis of the business policy framework. The economic performance is attributed to the discovery of a superior strategy and consistent with Chinese culture. The third part deals with a detailed description of the strategy and the structure. The strategy is actually a series of strategies: 1) a first level low-margin/high-volume strategy aimed at achieving a significant market share; 2) a second level strategy based on economies of scope, 3) a third level opportunistic strategy of business deals, and 4) a fourth level strategy dictated by the economic development plans of specific ASEAN countries. The effective structure devised by the Overseas Chinese in ASEAN is built on their twin areas of strength - entrepreneurship and the Chinese culture: 1) the use of social control systems, 2) the adoption of an entrepreneurial organization, and 3) the focus on the function of entrepreneurship by family members."--p. iii.
I. Thematic framework -- II. The history of the overseas Chinese in ASEAN -- III. The business policy hypothesis -- IV. The Chinese trading company -- V. The Chinese industrialists -- VI. The Chinese managerial system -- VII. Summary -- VIII. Areas for further research.
Keywords: Industrial management -- Southeast Asia; Chinese -- Economic conditions. -- Southeast Asia; Success in business -- Southeast Asia; Industrialists -- Southeast Asia; Merchants, Chinese -- Association of Southeast Asian Nations countries; Chinese in foreign countries